Factors Affecting Students’ Academic Performance in Higher Education: Evidence from Accountancy Degree Programme - Hassan, Haslinda; Mohamad, Rosli; Raja Mohd Ali, Raja Haslinda; Abdul Talib, Yurita Yakimin; Mohamad Hsbollah, Hafizah (International Business Education Journal, 2020)
The increasing demands for accountants in the future have resulted in an increased number of students enrolling in the accounting programmes of Malaysian universities. This expansion, however, has caused some concern about whether these students are likely to succeed in their studies. This study, therefore, aims to examine the factors that drive the academic performance of accounting students at Malaysian universities. The factors included gender, ethnic groups, type of secondary school, sponsorship, and family income. The students’ academic performance was represented by their cumulative grade point average (CGPA) obtained at the end of their programs. The study used a quantitative research design using secondary data of 367 undergraduate accounting students graduated in 2016 from the Universiti Utara Malaysia (UUM) for analysis. The findings suggested that there were significant differences in students’ academic performance related to ethnic groups, type of secondary school, and family income. Specifically, Malay, Indian, and other students performed less well than did Chinese students. Gender and sponsorship, however, had no significant influence on their academic performance. The study’s findings could help higher learning institutions, parents, and policymakers to formulate effective intervention mechanisms and to introduce a more holistic approach to improve student performance.